2019
DOI: 10.37604/jmsb.v1i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of three Aspergillus isolates against Fusarium wilt of banana

Abstract: Endophytic fungi have been known to play a role in protecting their host plants against diseases and extreme environments. The purpose of this study was to determine the antagonistic activity of three Aspergillus isolates against F. oxysporum f. sp. cubense (Foc), and to identify the Aspergillus identity using multilocus phylogeny analysis. Antagonistic assay by dual culture method showed that the Aspergillus sp. strain PD2, strain PD4, and strain PD5 inhibited the growth of Foc isolate by 37.31%, 26.52%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A. fumigatus has already been reported to secrete antifungal compounds able to inhibit pathogens, including Fusarium sp. [ 79 , 80 ]. On the other hand, isolates affiliated with F. solani were also found as a potential suppressive taxon in our system.…”
Section: Discussionmentioning
confidence: 99%
“…A. fumigatus has already been reported to secrete antifungal compounds able to inhibit pathogens, including Fusarium sp. [ 79 , 80 ]. On the other hand, isolates affiliated with F. solani were also found as a potential suppressive taxon in our system.…”
Section: Discussionmentioning
confidence: 99%
“…cubense (FOC) Aspergillus spp. strain PD2, PD4, and PD5 prevent fungal mycelia growth of FOC up to 37.31, 26.52 and 12.04% respectively [20].…”
Section: Molecularmentioning
confidence: 97%
“…have antagonistic potential against the pathogenic fungus Fusarium solani [8]. Hidayat et al [9] reported that endophytic fungi display antagonistic properties against pathogenic fungi. This is shown by the formation of inhibition zone between endophytic fungi and pathogenic microorganisms [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hidayat et al [9] reported that endophytic fungi display antagonistic properties against pathogenic fungi. This is shown by the formation of inhibition zone between endophytic fungi and pathogenic microorganisms [9]. Endophytic fungi can produce antibiotic compounds that inhibit pathogen growth by lysing the cell walls of pathogenic microorganisms [9,10].…”
Section: Introductionmentioning
confidence: 99%